Pengembangan Ekonomi Sirkular Pemanfaatan Limbah Serbuk Kayu untuk Budidaya Jamur Tiram untuk Meningkatkan Kesejahteraan Masyarakat dan Keberlanjutan Lingkungan - Nonon Saribanon; Noverita Noverita; Sara Pebrina; Isfan Fajar Sukarno; Fauziah Ilmi; Alvira Noer Effendi; Ichsan Wahyudin; Batari Wahyu Pangesti (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
This community service program was designed to empower residents of RW 06 Kalibaru, North Jakarta, by transforming local organic waste—such as sawdust and seashells—into a high-value commodity: oyster mushrooms. The training began with a needs assessment to ensure the relevance of the materials, followed by the application of the Adult Education (POD) approach, integrating theoretical and practical learning. The theoretical sessions provided participants with insights into economic prospects, nutritional benefits, and business opportunities, while the practical sessions developed technical skills in substrate preparation, sterilization, inoculation, and mushroom maintenance. The program was reinforced through participatory discussions, demonstrations, and simulations to ensure effective skill transfer. Monitoring and evaluation were conducted via Focus Group Discussions, and continuous mentoring was carried out through field visits, online communication, and the formation of farmer groups as collaborative platforms. As a result, participants demonstrated a significant improvement in knowledge and technical skills, accompanied by greater awareness of the economic potential of previously discarded waste. This initiative not only serves as an innovative solution to environmental problems but also acts as a catalyst for the application of the circular economy, creating micro-enterprise opportunities and strengthening community economic independence. The synergy between universities, the local community, and industry partners is a key factor in sustaining the program, with recommendations for expanding training on product diversification, marketing strategies, and policy support to accelerate business development. Additionally, the success of the program has opened new avenues for sustainable entrepreneurship, particularly in communities with limited resources. The involvement of local stakeholders—such as community leaders and small businesses—has been instrumental in fostering a sense of ownership and shared responsibility for the program's success. The use of organic waste as a resource for mushroom cultivation also aligns with broader environmental goals, such as reducing waste and promoting sustainable practices.